2021
DOI: 10.3389/fcvm.2021.676030
|View full text |Cite
|
Sign up to set email alerts
|

Association of Autism Spectrum Disorder, Neuroticism, and Subjective Well-Being With Cardiovascular Diseases: A Two-Sample Mendelian Randomization Study

Abstract: Background: Previous observational studies have reported an association between psychiatric traits and cardiovascular diseases (CVDs). In this two-sample Mendelian randomization (MR) study, we aimed to investigate the causality between psychiatric traits and CVDs.Methods: Single-nucleotide polymorphisms (SNPs) associated with autism spectrum disorder (ASD), neuroticism, and subjective well-being at genome-wide significance (P < 1 × 10−8) were identified from genome-wide association studies. Summary-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…In studies using non-fatal myocardial infarction (MI) as an endpoint, neuroticism was the only trait significantly associated with the incidence of MI 22 . On the other hand, a recent Mendelian randomization study found casual associations between neuroticism and the prevalence of atrial fibrillation, while no significant associations were detected with other CVDs such as myocardial infarction (MI) or coronary artery disease 23 . Thus, larger population-based studies are needed to clarify the mediating role of personality in development and progression of specific CVDs.…”
Section: Introductionmentioning
confidence: 98%
“…In studies using non-fatal myocardial infarction (MI) as an endpoint, neuroticism was the only trait significantly associated with the incidence of MI 22 . On the other hand, a recent Mendelian randomization study found casual associations between neuroticism and the prevalence of atrial fibrillation, while no significant associations were detected with other CVDs such as myocardial infarction (MI) or coronary artery disease 23 . Thus, larger population-based studies are needed to clarify the mediating role of personality in development and progression of specific CVDs.…”
Section: Introductionmentioning
confidence: 98%
“…Prospective studies have previously demonstrated that several psychiatric conditions (e.g., depression 7,8 , schizophrenia 9 , bipolar disorder 10 , and anxiety disorders 11 ) as well as neurodevelopmental disorders (e.g., autism 12,13 , intellectual disabilities 12 , and conduct disorder 12 ) are associated with a higher risk for cardiovascular diseases, the leading cause of mortality worldwide 14 . The mechanisms linking psychiatric illness to cardiovascular diseases are complex, but risky health behaviours (e.g., smoking, drinking alcohol, substance abuse, and sedentary lifestyles) 15 and prolonged use of psychotropic medications 16 have been proposed as potential contributors to the risk.…”
mentioning
confidence: 99%
“…Recently, a two-sample MR study suggested depression was associated with increased CAD risk. [18], and another MR study showed that neuroticism was casually associated with a higher risk of atrial fibrillation [19]. However, no MR studies have explored the causality between mental health and CAD in patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%